2021
DOI: 10.3390/s21093130
|View full text |Cite
|
Sign up to set email alerts
|

A System for Neuromotor Based Rehabilitation on a Passive Robotic Aid

Abstract: In the aging world population, the occurrence of neuromotor deficits arising from stroke and other medical conditions is expected to grow, demanding the design of new and more effective approaches to rehabilitation. In this paper, we show how the combination of robotic technologies with progress in exergaming methodologies may lead to the creation of new rehabilitation protocols favoring motor re-learning. To this end, we introduce the Track-Hold system for neuromotor rehabilitation based on a passive robotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…As described above, state of the art indicates that the combination of RAT with exergames might have a beneficial outcome. In consideration of our previous work [ 2 ] in which a specific suite of exergames was designed for use with the Track Hold System, in this paper, we extend the experimental results by proposing a pilot study and analyzing the impact of our methodology in improving upper limb motricity.…”
Section: State Of the Art In Robotic Assisted Therapy (Rat)mentioning
confidence: 97%
See 1 more Smart Citation
“…As described above, state of the art indicates that the combination of RAT with exergames might have a beneficial outcome. In consideration of our previous work [ 2 ] in which a specific suite of exergames was designed for use with the Track Hold System, in this paper, we extend the experimental results by proposing a pilot study and analyzing the impact of our methodology in improving upper limb motricity.…”
Section: State Of the Art In Robotic Assisted Therapy (Rat)mentioning
confidence: 97%
“…The device consists of arms connected by joints. Each of the joints is equipped with a patented precision angle sensor [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ritchie et al [ 8 , 9 ] developed a passive robotic arm capable of recording and facilitating the movement of the upper extremity to aid in the rehabilitation of the upper extremity after stroke. Another line of scholars [ 10 , 11 ] have suggested that robotic-assisted therapy may help improve arm and function in patients with cervical spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%